ILRI research on animal diseases in Africa—Accomplishments and partnerships - Pelle, Roger (International Livestock Research Institute, 2011)
For the November 2011 'liveSTOCK Exchange' event at the International Livestock Research Institute (ILRI), Roger Pellé, reflects on ILRI's biotechnology research accomplishments, from the past 10 years, that involved partnerships with other centres and countries in Africa.